Disability among elderly rural villagers: report of a survey from Gonoshasthaya Kendra, Bangladesh - Cherry Nicola; Chowdhury Morshed; Haque Rezaul; McDonald Corbett; Chowdhury Zafrullah (BMC Public Health, 2012)
Abstract Background The study was set up to identify the extent and nature of difficulty with activities of daily living (disabilities) among elderly village residents of Bangladesh, to describe help currently given and to identify possible interventions. It was carried out at Gonoshasthaya Kendra (GK), a community development organization responsible for the health care of 600 villages with a population of some 1.5 million. Methods A survey card was designed and piloted using 12 questions on disability, elaborated from the Washington Group Disability questions, together with a checklist of health problems. A survey was carried out in 2010 in 535 villages under the care of GK since 2005, with village paramedics interviewing residents believed to be age 60 years or older. Respondents were matched where possible to data from the 2005 GK household census, giving data on education, occupation, socioeconomic group and smoking habit. Results Survey cards were completed for 43417 residents of which 17346 were matched to residents recorded in the GK census as born ≤ 1945. The proportion reporting ‘much difficulty’ on one or more functional capacities increased steadily with age, reaching 55% (1796/3620) among those ≥ 85 years. Difficulties most frequently reported were lifting and carrying, vision and going outside the home. At all ages women were more likely to report ‘much difficulty’ than men (OR = 1.43 (1.35 to 1.48)), with widows and the illiterate at greater risk. Health problems, particularly hemiplegia, resting tremor, urinary incontinence and depression were strongly related to the 12 disabilities assessed. Help came almost entirely from family members; of 11211 villagers with ‘much difficult’ on at least one functional capacity, only 15 reported getting help outside the family. Conclusions Disabled elderly residents were dependent on the family for help but, with family cohesiveness under threat from migration to the city, there is a pressing need for the development and critical evaluation of community-based interventions designed specifically for the elderly in poor rural societies. New approaches to training and practice will be needed to integrate such disability management into primary care.